2016
DOI: 10.1021/acs.jced.5b00894
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Solubility of Carbon Dioxide in Nitrate and Thiocyanate-Based Ionic Liquids

Abstract: New experimental results are reported for the solubility of carbon dioxide (CO 2 ) in nitrate-and thiocyanatebased ionic liquids (ILs) at temperatures ranging from 298.15 to 333.15 K and pressure up to 4.5 MPa. The studied ILs are 1-, and 1-butyl 3-methylimidazolium tetrafluoroborate [Bmim][BF 4 ]. The solubility measurements are performed in a known volume stainless steel equilibrium cell. The experimental data indicated the solubility of CO 2 decreases with increasing of temperature. Henry's constant are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The experimental thermodynamic derivative properties and the experimental solubility of one gas in one IL were surveyed and collected thoroughly. The information on the available experimental results …”
Section: Experimental Data Surveymentioning
confidence: 99%
“…The experimental thermodynamic derivative properties and the experimental solubility of one gas in one IL were surveyed and collected thoroughly. The information on the available experimental results …”
Section: Experimental Data Surveymentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) emission from anthropogenic sources is driving concerns over climate change, as this greenhouse gas has reached atmospheric concentration levels never observed before . Current efforts aimed at the mitigation of this gas involve developing materials and reagents capable of reversible binding to CO 2 in a strategy known as carbon capture and storage (CCS). , The sequestration of carbon dioxide is currently being explored using various agents, including polyamine adsorbent materials, ionic liquids, , frustrated Lewis pairs, , and metal-organic frameworks . While the aforementioned materials exhibit enhanced binding to CO 2 , it is also important that this binding be weak enough to permit the conversion of this gas into other usable chemicals and/or fuels as part of a broader carbon capture and utilization process (CCU).…”
Section: Introductionmentioning
confidence: 99%
“…Blanchard et al, the first scientists that studied on CO 2 absorption of ILs, reported that the mole fraction of CO 2 in 1‐butyl‐3‐methylimidazolium hexafluorophosphate [Bmim][PF 6 ] at 8 MPa is 0.6 . A lot of following studies on CO 2 absorption in ILs have been published . Aki et al found that an increase in the length of the alkyl chain located on imidazolium cation leads to the increase of CO 2 absorption capacity .…”
Section: Introductionmentioning
confidence: 99%